Evaluación de los riesgos psicosociales relacionados con la carga laboral en el área administrativa, del distrito de salud 02d03, chimbo-san miguel, para la implementación de medidas preventivas. - Guerrero Castillo, Ramiro Patricio (2017)
The present investigation consists in the evaluation of the psychosocial risks related to the workload in the administrative area of the Health District 02D03, Chimbo-San Miguel, for the implementation of preventive measures. The research was developed applying 4 methods validated by the INSHT that are methodology LEST, R.N.U.R, INSHT, and modified COOPER-HARPER SCALE. The applied methods evaluate the psychosocial risks under different guidelines. In order to obtain a comparable assessment of the level of psychosocial risk within the administrative area of the Health District 02D03, the units were converted from the risk level of each of the methodologies to equivalent units of general risk, based on the level of performance Of each risk, obtaining the results of the risk assessment on a single scale of all methodologies. In order to verify that there are no statistical differences between the results of the level of risk on a general scale, ie, to verify that all methods showed an equal level of psychosocial risk, we proceeded to apply the ANOVA test. When testing the risk level in the general scale of the methodologies applied in the risk assessment, a significance value of 0.1546 (sig> 0.05) was obtained, therefore there were no significant differences. In view of the fact that there were no statistical differences between the means of the psychosocial risk level registered through the different evaluation methodologies, it can be pointed out that the applied methodologies generated equal values in the level of psychosocial risk, which on average was equal to 2. This leads to the conclusion that the psychosocial risks within the administrative area of the Health District 02D03 are controlled, and the working environment conditions can be improved if there is a technical and economic support